(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research seeks to shed light on the important issue of social service issues, namely how the scientific and professional proper handling of social intervention and solving some of the social problems that you may encounter individuals or families, or reduce the severity of these problems as much as possible through the so-called (general practice in modern social service) where is the general practice in the social service of the newest specialized programs currently in place in developed countries, which seeks to train researchers or specialists meetings in possession of solving the social problem skills, according to a holistic approach fits the capabilities available, and addresses the needs of the beneficiaries (the owners of the problems) . This paper introduced a practical model and realistic about the social problem on the individual and household level , and shows the stages of social intervention from the perspective of general practice and the development of social intervention plan suits the studied case, aimed at solving or alleviating the problems of this family . Use this search phases of modern social intervention currently applied in developed countries was the most important of search results that it has been most of the problems faced by the family that has been studied exceeded , so the general practice are suitable to solve family problems working mechanism .